Serum homocysteine levels in patients with probable vascular dementia - Salem Alajbegović; Orhan Lepara; Almira Hadžović-Džuvo; Alma Mutevelić-Turković; Lejla Alajbegović; Asija Zaćiragić; Nesina Avdagić; Amina Valjevac; Nermina Babić; Amela Dervišević (Medicinski glasnik, 2017)
Aim: To investigate total homocysteine (tHcy) serum concentration in patients with probable vascular dementia (VD) and in agematched controls, as well as to determine an association between tHcy serum concentration and cognitive impairment in patients with probable VD. Methods: Serum concentration of tHcy was determined by the Fluorescence Polarization Immunoassay on the AxSYM System. Cognitive impairment was tested by the Mini Mental Status Examination (MMSE) score. Body mass index (BMI) was calculated for each subject included in the study. Results: Age, systolic, diastolic blood pressure and BMI did not differ significantly between the two groups. Mean serum tHcy concentration in the control group of subjects was 13.35 µmol/L, while in patients with probable VD it was significantly higher, 19.45 µmol/L (p=0.002). A negative but insignificant association between serum tHcy concentration and cognitive impairment in patients with probable VD was found. Conclusion: Increased tHcy concentration in patients with probable VD suggests the possible independent role of Hcy in the pathogenesis of VD.
Keywords: neurotoxicity; cognitive impairment; Mini-Mental State Examination